2021
DOI: 10.7759/cureus.14950
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Account of Obstetrical and Gynecological Specimens: Retrospective Study at a Tertiary Care Center of Peshawar

Abstract: IntroductionHistopathologic specimen examination of surgically isolated organs and tissues yields valuable information regarding a disease process and plays a vital role in the future management of a patient. Our aim was to account for the common diagnosis yielded from histopathological specimens of the obstetrics and gynecology department and to determine if all the obstetric and gynecological specimens should be routinely sent for histopathology. MethodsA retrospective, cross-sectional study was conducted at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Nasim and coauthors in a study from Peshawar, Pakistan reported similar incidence (92.4%) of chronic cervicitis. 17 Their study reported 3 malignancies of cervix; 2 were squamous cell carcinoma, and 1 was adenocarcinoma. In a previous study from Tamil Nadu chronic cervicitis was seen in 85% of hysterectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Nasim and coauthors in a study from Peshawar, Pakistan reported similar incidence (92.4%) of chronic cervicitis. 17 Their study reported 3 malignancies of cervix; 2 were squamous cell carcinoma, and 1 was adenocarcinoma. In a previous study from Tamil Nadu chronic cervicitis was seen in 85% of hysterectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous conditions such as abnormal uterine bleeding, pelvic pain, pelvic inflammatory disease (PID), prolapse of the uterus, adenomyosis, endometriosis, fibroids, gynecological malignancies, and obstetric problems have been reported. Every hysterectomy sample must be examined histopathologically because histology is the only source of the final diagnosis [ 5 ]. Histopathological examination of the specimens obtained after hysterectomy is important for both diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%